Modification of a Brazilian natural clay and catalytic activity in heterogeneous photo-Fenton process - Rojas-Mantilla, Hernán D. [UNESP]; Ayala-Duran, Saidy C. [UNESP]; Pupo Nogueira, Raquel F. [UNESP] (Elsevier, 2022)
The catalytic activity of a Brazilian natural clay modified with the immobilization of iron oxide was applied in the heterogeneous Fenton process for the degradation of the antibiotic sulfathiazole (STZ). The clay without any treatment indicated a lamellar type material with mesoporous distribution that presents a heterogeneous mixture of phases (type 1:1 and 2:1 structures), with a predominance of quartz, montmorillonite, gibbsite and kaolinite, and with SiO2, Al2O3, Fe2O3, K2O, TiO2, MgO as major oxides. Its high absorption in the UV–Vis ranges with a bandgap energy of 1.9 eV was attributed to the presence of hematite. It was observed that the effects of the addition of starch before heat treatment, and impregnation with iron, modified the clay surface. F rom the X-ray photoelectron spectroscopy analysis it was concluded that a structural reorganization is related to the conversion of the various iron oxide phases into hematite, as well as promoting an increase in Fe2+/ Fe3+ redox reactions allowing rapid degradation of STZ. The catalyst impregnated with iron and treated at 600 °C showed to be an economical and versatile catalyst with high catalytic efficiency (>97% STZ degradation after 60 min), with small differences according to the type of LED device used. Furthermore, it presented high stability and reusability reaching 93% degradation of STZ after four cycles of reuse with low consumption of H2O2.
Keywords: Catalytic support; Hydroxyl radical; Iron oxide; Kaolinite; Montmorillonite